KESESUAIAN ISI BUKU TEKS BAHASA INDONESIA SMK/MAK TERBITAN YUDHISTIRA DENGAN KURIKULUM 2013 - Nur Sakinah; Ahadi Sulisusiawan; Abdussamad Abdussamad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractNur Sakinah, 2021. The suitability of the contents of the SMK/MAK textbook published by Yudhistira with the 2013 curriculum. Indonesian Language Education Study Program, Department of Language and Arts Education, Faculty of Teacher Training and Education, University of Tanjungpura Pontianak. First Advisor Dr. Ahadi Sulissusiawan, M.Pd Second Advisor Adussamad, M.Pd. This study examines the contents of textbooks that discuss the suitability of basic competencies in material coverage, as well as the flow of genre, scientific and CLIL pedagogical approaches in textbooks with the 2013 curriculum syllabus. This study aims to analyze the suitability of basic competencies, material coverage, and the flow of genre, scientific pedagogical approaches. and CLIL in the textbook with the 2013 curriculum syllabus. The research method used is descriptive with a qualitative research form. The data sources of this research are Indah Wukir Setiarini and Santi Artini who wrote textbooks. Sources of data are obtained indirectly through the results of the textbooks that are made. The data collection technique used is indirect technique with documentation study. The data collection tools used were stationery and a list of notes. The results of the analysis show that in general the textbook cannot be said to be suitable because in the presentation of basic competencies, material coverage, and the flow of the pedagogical approach to genre, science and CLIL, there are parts that are not found in the textbook either directly or implicitly. Based on the results of the analysis that has been done,schools are advised in selecting school textbooks to first see the extent to which the textbooks that will be used conform to the syllabus. Teachers are advised not only to refer to the books given by the school but to use other literature sources that can complement a subject in learning. Publishers are advised in the process of compiling publisher textbooks based on the syllabus.Keywords: Content Suitability, Textbook, 2013 Curriculum